Population imaging of enterochromaffin cell activity reveals regulation by somatostatin - Nathan D. Rossen; Kouki K. Touhara; Joel Castro; Andrea M. Harrington; Sonia Garcia Caraballo; Fei Deng; Yulong Li; Stuart M. Brierley; David Julius (Proceedings of the National Academy of Sciences, 2025)
Sensory enteroendocrine cells in the intestinal epithelium detect and relay information about the luminal environment to other cells within and outside the gut. Serotonergic enterochromaffin (EC) cells are a subset of enteroendocrine cells that detect noxious stimuli within the gut lumen, such as chemical irritants and microbial byproducts, and transduce this information to sensory nerve fibers to elicit defensive responses such as nausea and visceral pain. While much has recently been learned about the pharmacological and biophysical characteristics of EC cells, a more broadscale investigation of their properties has been hindered by their relatively low prevalence and sparse anatomical distribution within the gut epithelium. Here, we introduce a method for large-scale parallel analysis of individual EC cell activity within a physiologically relevant epithelial context. Using this approach, we identify somatostatin-28 as a potent inhibitor of both basal and stimulus-evoked serotonin release from EC cells and delineate the signaling pathway that underlies this modulatory response. Our analysis suggests that targeting this inhibitory signaling pathway may offer therapeutic avenues for treating gastrointestinal disorders associated with EC cell function and dysregulated serotonin signaling. Together with the ongoing development of specific biosensors, this platform provides a template for the efficient characterization of other rare sensory cell types and their pharmacological modulators.